PENGARUH EFEKTIFITAS SISTEM DROP BOX SEBAGAI SARANA PELAPORAN SPT TAHUNAN TERHADAP KEPATUHAN WAJIB PAJAK - Zaena, Rosye Rosaria; Dini, Dicky Frans (Jurnal Riset Akuntansi, 2015)
The purpose of this research was to determine how much the effectiveness drop box system of tax compliance in the Tax Office Pratama Bandung Cicadas. The method used in this research is survey method, verifivative and explanatory research. The test statistic used is regression model, and hypotheses using software SPSS 19. These results indicate that effectiveness drop box system has a significant positive effect on the tax compliance in the Tax Office Pratama Bandung Cicadas. Keywords: Drop box system, tax compliance